Amor Amazónico (2025)
“Amazonian Love” is a feature-length fiction screenplay subscribed in the romantic drama genre that explores how love and memory can redefine human identity. Set in the Colombian Amazon, the story follows Andres, a man who loses his memories after an accident, and Laura, who, after this tragic event, seeks to reconstruct her past by reconnecting with the territory and the indigenous world. Through Macuna's community cosmovision, the story raises questions about the endurance of human bonds beyond time and loss.